Rethinking European Competition Law: From a Consumer Welfare to a Capability Approach - Rutger Claassen (Utrecht Law Review, 2016)
European competition law is predominantly focused on maximizing consumer welfare. This overarching purpose (which is supported by economic theory) leaves little place for safeguarding non-economic values, such as sustainability. This makes it difficult to allow cooperation between companies to contribute to such non-economic goals. In this article we explore whether it is possible to establish a different normative framework, in which such goals can be taken into account and can be balanced against the economic goal of consumer welfare. To answer this question, we take four steps. First, we discuss current EU competition law and the difficulty of fitting non-economic goals into the dominant interpretation of that law. Second, we propose a different normative framework, based on the capability approach advanced by philosopher Martha Nussbaum and economist Amartya Sen. Third, we argue that there are good principled reasons to incorporate non-economic goals into competition law. Fourth, we apply both the capability approach and the consumer welfare approach to three (illustrative) cases in which non-economic goals are at stake. Overall, we argue that the capability framework, although not without difficulties of its own, may provide a more legitimate theory for the interpretation of European competition law.